Theoretical study of the sequence-dependent distribution of Na+ ions around DNA - Hui-ting Xu; Xiao-wei Jiang; Yu-jie Song; Bin Gu (Results in Chemistry)
Sodium ions play a crucial role in diverse biological processes. This study focuses on the sequence-dependent distribution of sodium ions around DNA, utilizing the bsc0 force field to simulate and accurately replicate the conformational changes observed in Raman spectroscopy experiments, and provides an explanation for the phenomenon of bimodal distribution of pAC sequences. Molecular dynamics simulations revealed that Na+ ions exhibiting unique distributions in pAA, pGA, and pGG oligomers. These ions progressively shift from the phosphate group and minor groove towards the G-tract region of the major groove. Significantly, the pGC sequence exhibits a transition in Na+ ion distribution from the major to minor grooves. The overall binding of sodium ions to the pAC sequence is weak. The pAT sequence reduces the ionic affinity in the groove, and a small portion is distributed near the ATA·TAT base order in the minor groove. The study determined a 75 % neutralization rate across DNA oligonucleotides, independent of sequence. Analyses of weak interactions revealed stable G·C and A·T hydrogen bonds alongside diminished C-H···O bonds, and a reduction in base pair stacking interaction with sequence variation. Sodium ions bind to DNA with over 95 % electrostatic interaction energy, the pAA oligomer exhibits the lowest interaction energy. The distribution of water molecules around DNA is less affected by sequence. The study provides a deep atomic-level understanding of the behavior of sodium ions around DNA.